Feasibility study on the utilization of mahogany (Swietenia macrophylla King) wood as a raw material in the bio-oil production. (June 2020) - Kadarwati, S; Qurrochman, T; Kurniawan, C; Jumaeri,; Kasmui,
Abstract: The liquid fuels from biomass produced through fast pyrolysis is very promising due to their high energy density and carbon neutral properties. Therefore, the pyrolysis of Indonesian mahogany wood at various temperatures (450-600°C) was carried out in this study. A fixed-bed reactor was used in the pyrolysis experiments. The produced bio-oil, bio-char, and gaseous product were recovered and quantified. This study showed that the higher the temperature, the higher the yield of the bio-oil (39.40 wt% at 550°C). However, the pyrolysis at a temperature higher than 550°C produced a lower yield of bio-oil, possibly due to severe cracking resulting in more gaseous products. The produced bio-oils showed good characteristics, i.e. density of c.a. 1, 17 g/mL, viscosity of 3.93-5.67 poise, total acid number of 0.66-0.79 mg-KOH/g, and calorific value of 16-18 MJ/kg. The water and volatile (acetic acid, furfural, phenol, and stearic acid) contents of the produced bio-oils were also quantified by using a gas chromatograph. The bio-oils with a low water content (13.46-15.90 wt%) and volatiles (0.1-2.9 wt%) were obtained, indicating high energy density and production of heavy molecules, respectively. The high acid number was likely from the heavy acids that could not be detected by the gas chromatograph.